2019
DOI: 10.3390/ijms20051154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of miR-98-5p, miR-152-3p, miR-326 and miR-4289 Expression as Biomarker for Prostate Cancer Diagnosis

Abstract: Prostate cancer (PCa) is one of the most commonly diagnosed cancers worldwide, accounting for almost 1 in 5 new cancer diagnoses in the US alone. The current non-invasive biomarker prostate specific antigen (PSA) has lately been presented with many limitations, such as low specificity and often associated with over-diagnosis. The dysregulation of miRNAs in cancer has been widely reported and it has often been shown to be specific, sensitive and stable, suggesting miRNAs could be a potential specific biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 83 publications
1
44
0
Order By: Relevance
“…Melatonin targets miR-152-3p and represses angiogenic factors in triple-negative breast cancer [21]. Intriguingly, MiR-152-3p was also a tumor inhibitor in glioma [22], prostate cancer [23] and triple-negative breast cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin targets miR-152-3p and represses angiogenic factors in triple-negative breast cancer [21]. Intriguingly, MiR-152-3p was also a tumor inhibitor in glioma [22], prostate cancer [23] and triple-negative breast cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, hsa-miR-520 was demonstrated to play role in regulating proliferation and migration of lung cancer and modulating progression of renal carcinoma while there was no evidence about this miRNA and GC [28,29]]. And miR-98 could be served as biomarker for prostate cancer diagnosis and it may up-regulated in GC, which was involved in the development and progression of GC [30,31]. Let-7 miRNA family played a central role in the regulatory relationships between miRNAs and mRNAs in GC, and hsa-let-7c was associated with the clinicopathological parameters of GC [32].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of gene signatures, the prognosis of some types of cancer has been predicted by statistical models. MiR-98-5p, miR-152-3p, miR-326 and miR-4289 Expression could serve as Biomarker for Prostate Cancer Diagnosis [21]. We also performed GSEA analysis using the mRNA expression data of the 503 LUSC patients and found that 4 exhibit signi cant differences, with a P value <0.05, and the minimum P value could be used for further analysis.…”
Section: Discussionmentioning
confidence: 99%